Church laws and ecumenism : a new path for Christian unity - Doe, Norman (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"The ecumenical movement, with its historical theological focus, has failed to-date to address the role of church law in shaping relations between churches and fostering greater mutual understanding between them. In turn, theologians and jurists from the different traditions have not hitherto worked together on a fully ecumenical appreciation of the potential value of church laws to help, and sometimes to hinder, the achievement of greater Christian unity. This book seeks to correct this ecumenical church law deficit. It takes account of the recent formulation by an ecumenical panel of a Statement of Principles of Christian Law which has been welcomed by Pope Francis and the Ecumenical Patriarch of Constantinople, leader of the Orthodox Church worldwide, as recognizing the importance of canon law for ecumenical dialogue. This book, therefore, provides not only the fruits of an understanding of church laws within ten Christian traditions, but critically evaluates the Statement against the laws of these individual ecclesial communities"--
Introduction / Norman Doe -- The evolution of the principles of Christian Law / Norman Doe -- Roman Catholic Canon Law / Aidan McGrath OFM and Robert Ombres OP -- The Law of the Eastern Catholic Churches / Astrid Kaptijn -- The Orthodox Canonical Tradition / Nikos Maghioros -- The Anglican Canonical Tradition / Mark Hill -- Lutheran Church Law / Andreas Aarflot -- Methodist Law and Discipline / John Harrod -- Reformed Church Order / Leon van den Broeke -- Presbyterian Polityand Practice / John Chalmers -- Baptist Church Polity / Paul Goodliff -- Pentecostal Church Polity / Paul Rochester -- The Polityofthe United and Uniting Churches / Leo J.Koffeman -- Conclusion / Aetios, Grand Ecclesiarch of the Ecumenical Patriarchate of Constantinople.
OCLC-licensed vendor bibliographic record.
Keywords: Comparative canon law; Ecumenical movement; LAW / General; LAW / Comparative; LAW / Jurisprudence